PROGRESSIVE STEP MAXIMUM POWER TRACKER FOR CASCADED INVERTER INDUCTION MOTOR DRIVE: PROGRESSIVE STEP MAXIMUM POWER TRACKER FOR CASCADED INVERTER INDUCTION MOTOR DRIVE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This paper presents the idea of an isolated photovoltaic (PV) based cascaded two-level inverter (CTLI), driving squirrel cage induction motor (SCIM). The connected non-linear load approximately represents a centrifugal pump. The control system of this drive is based on a motor control system along with a progressive step perturb and observe (PSPnO) maximum power point tracking (MPPT) technique for the PV sources towards better utilization of the source. This PSPnO MPPT system intends to operate the SCIM so that the energy developed by PV is utilized entirely through variation of the dc-link voltages of the CTLI under both uncertain variances of non-linear load torque and unpredictable solar irradiance. This PSPnO MPPT algorithm has been engaged in the control scheme for generating reference dc-link voltage. This motor control system is designed to operate in a rotor-flux-oriented rotating reference frame. As for generating CTLI’s switching pulses, the space vector pulse width modulation (SVPWM) technique has been used for its good dynamic response. The whole system is designed to be deployable on a low-computation device. The simulations conducted by Simulink and the results are furnished considering various operational conditions.
Keywords: Induction motor; Photovoltaic (PV); Progressive step; Perturb and observe; Maximum power point tracking (MPPT); Non-linear load